2016
DOI: 10.1175/jcli-d-15-0524.1
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Modes of Interannual Variability in Eurasian Surface Air Temperature during Boreal Spring

Abstract: This study investigates interannual variations of surface air temperature (SAT) over mid-and high latitudes of Eurasia during boreal spring and their association with snow, atmospheric circulation, and sea surface temperature (SST) changes. The leading mode of spring SAT variations is featured by same-sign anomalies over most regions. The second mode features a tripole anomaly pattern with anomalies over the central part opposite to those over the eastern and western parts of Eurasia. A diagnosis of surface he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
139
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(146 citation statements)
references
References 35 publications
(28 reference statements)
7
139
0
Order By: Relevance
“…However, the relationship between the dominant modes of Eurasian snow and atmospheric circulation during autumn and spring is still not clear. In addition, a better understanding of the snow-atmosphere coupling mode demands a deeper insight into the associated boundary thermal conditions (Chen, Wu, and Liu 2016).…”
Section: Seasonal Evolution Of the Eurasian Snow And Circulation Domimentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationship between the dominant modes of Eurasian snow and atmospheric circulation during autumn and spring is still not clear. In addition, a better understanding of the snow-atmosphere coupling mode demands a deeper insight into the associated boundary thermal conditions (Chen, Wu, and Liu 2016).…”
Section: Seasonal Evolution Of the Eurasian Snow And Circulation Domimentioning
confidence: 99%
“…Excessive autumn and winter Eurasian snow cover can cause a negative-phase winter AO mode, and vice versa (Saito, Cohen, and Entekhabi 2001;Cohen et al 2007). On the other hand, the AO/NAO mode also exerts important influence on the Eurasian snowpack variability as the Eurasian continent is warmer in the positive-phase AO (Clark, Serreze, and Robinson 1999;Kim, Kim, and Kim 2013;Chen, Wu, and Liu 2016). A consensus has been reached that the Eurasian snow cover variability is more dependent on temperature than on precipitation (Walland and Simmonds 1997;Henderson and Leathers 2010;Yeo, Kim, and Kim 2017).…”
Section: Introductionmentioning
confidence: 99%
“…SAT variations over Eurasia were impacted by lower boundary factors, including Eurasian snow cover (Chen et al, ; K. Ye et al, ), the Arctic sea ice (Chen & Wu, ; J. P. Liu et al, , C. Sun et al, ; J. Zuo et al, ), and sea surface temperature (SST) in the North Atlantic and Pacific (Chen et al, , ; Graf & Zanchettin, ; R. Wu & Chen, ; R. Wu et al, , ). Above mentioned studies generally showed that atmospheric circulation anomalies play an important role in relaying the impacts of the Arctic sea ice and SST on the Eurasian SAT.…”
Section: Introductionmentioning
confidence: 99%
“…Above mentioned studies generally showed that atmospheric circulation anomalies play an important role in relaying the impacts of the Arctic sea ice and SST on the Eurasian SAT. R. Wu et al () and Chen et al () indicated that the North Atlantic SST anomalies influence the Eurasian SAT variations via triggering an atmospheric wave train over the North Atlantic through the Eurasia. J. Zuo et al () reported that preceding autumn Arctic sea ice anomalies have a significant influence on the subsequent winter temperature variations over China via modulating the Siberian High and the East Asian trough.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation